2022
DOI: 10.1002/aenm.202200660
|View full text |Cite
|
Sign up to set email alerts
|

Super Long‐Cycling All‐Solid‐State Battery with Thin Li6PS5Cl‐Based Electrolyte

Abstract: high interfacial impedance between SSEs and electrodes, and relatively high fabrication cost, which impede their applications. SSEs with high ionic conductivity, wide electrochemical window and low interfacial impedance are critical in developing ASSBs with high specific energy and power density. [2,3] Currently, among various SSEs, sulfide SSEs have a Li-ion conduction capability comparable to that of organic liquid electrolytes (≈10 -2 S cm -1 at room temperature). [4][5][6][7][8][9][10] Various sulfide ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 60 publications
(49 reference statements)
0
61
0
Order By: Relevance
“…Nan and his colleague constructed a three-dimensional poly(vinylidene fluorideÀ cotrifluoroethylene) P(VDFÀ TrFE) network composed of argyrodite Li 6 PS 5 Cl (LPSCl) by electrospinning-infiltration-hot-pressing method. [70] Interaction of polar P(VDFÀ TrFE) and LPSCl not only generates high ionic conductivities, but also produce good mechanical and reach the thickness of 30-40 μm.…”
Section: Poly(vinylidene Fluoride)-based Polymer Electrolytesmentioning
confidence: 99%
“…Nan and his colleague constructed a three-dimensional poly(vinylidene fluorideÀ cotrifluoroethylene) P(VDFÀ TrFE) network composed of argyrodite Li 6 PS 5 Cl (LPSCl) by electrospinning-infiltration-hot-pressing method. [70] Interaction of polar P(VDFÀ TrFE) and LPSCl not only generates high ionic conductivities, but also produce good mechanical and reach the thickness of 30-40 μm.…”
Section: Poly(vinylidene Fluoride)-based Polymer Electrolytesmentioning
confidence: 99%
“…There are three types of ternary high nickel cathode materials: LiNi 0.5 Mn 0.3-Co 0.2 O 2 (NCM 523 ), 76,77,[86][87][88] LiNi 0.6 Mn 0.2 Co 0.2 O 2 (NCM 622 ) 89-94 and LiNi 0.8 Mn 0.8 Co 0.1 O 2 (NCM 811 ). [95][96][97][98][99][100] In these three types of ternary cathode materials, Ni has two valence states, namely +2 and +3, while Co is in its +3 state and Mn still maintains its +4 state, which is used to keep the material structure stable. When the charging voltage is lower than 4.4 V, Ni 2+/3+ is oxidized to Ni 4+ in the reaction.…”
Section: High Nickel Ternary Cathode Materialsmentioning
confidence: 99%
“…Zhang et al have revealed the evolution of the space charge layer of NCM811/ Li 6 PS 5 Cl /Li batteries by in situ electrochemical impedance spectroscopy and Raman spectroscopy. [173] In the early stage of the cycle, the space charge layer is the main factor affecting the deterioration of the battery interface. The migration and redistribution of Li + at the interface caused by the space charge layer (Li + transfers from the sulfide side to the oxide side) leads to the interfacial change of PS bond state in the sulfide electrolyte Li 6 PS 5 Cl.…”
Section: Solid Electrolytesmentioning
confidence: 99%
“…The migration and redistribution of Li + at the interface caused by the space charge layer (Li + transfers from the sulfide side to the oxide side) leads to the interfacial change of PS bond state in the sulfide electrolyte Li 6 PS 5 Cl. [173] The increase in battery cycles, interfacial reactions, mechanical failures, and dendrite growth lead to the deterioration of the interface, resulting in the degradation of battery performance. This in-depth interfacial research work provides an important theoretical reference for optimizing all-solid-state batteries.…”
Section: Solid Electrolytesmentioning
confidence: 99%